Acetone Gas Sensing Using a Hybrid Mid-Infrared Fluoride Fiber Laser - Theodosiou, Andreas; Kalli, Kyriacos; Sapir-Henderson, O. (My University, 2024)
Our recent advancements in the development of a hybrid mid-infrared (mid-IR) fiber laser setup tailored specifically for the measurement of acetone gas concentrations are presented. The laser configuration incorporates a fiber Bragg grating (FBG) inscribed in an erbium-doped zirconium fluoride fiber, achieved through the direct-write plane-by-plane femtosecond laser inscription method, coupled with a free-space broadband reflection. By employing the dual-wavelength pumping technique, the laser system demonstrated good performance, generating an output power exceeding 500 mW and exhibiting a slope efficiency of 15.2%. Utilizing this setup, we successfully detected acetone vapor at 3.46-μ m absorption band. The versatility demonstrated by this scheme underscores its potential for future applications in multifaceted breath analysis applications, showcasing a promise for extensive multicompound analysis.
Keywords: Acetone sensing; breath analysis; fiber Bragg gratings (FBGs); fiber lasers; gas sensing; mid-infrared (mid-IR) lasers